Management Commitment, Philanthropic Value Chain Integration, and Trust Capital for Sustainable Zakat Institutions in Indonesia - Ahmad Said; Khomsiyah; Nirdukita Ratnawati; Zulpahmi (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study examines the effects of trust capital, philanthropic value chain integration, and management commitment on the sustainable value chain practices of Zakat Collection Institutions (LAZ) to optimize ZISWAF operational governance in Indonesia. Employing a quantitative correlational survey design and partial least squares structural equation modelling (PLS-SEM) using SmartPLS 3.0, data were collected from a purposive sample of 186 key management and operational personnel in the Greater Jakarta region. The measurement model demonstrated strong reliability and validity for all indicators. Structural path analysis revealed that management commitment, philanthropic value chain integration, and trust capital each have positive and statistically significant effects on sustainable practices, resulting in a model with high predictive relevance. The findings offer a practical framework for LAZ administrators to improve intra-organizational synergy, optimize resource allocation, and utilize stakeholder trust to foster an accountable, high-impact charitable ecosystem. This research contributes novel insights by adapting conventional supply chain paradigms into a faith-based philanthropic value chain framework and by identifying trust capital as a direct operational antecedent to nonprofit governance.